The Efficiency of Web-based instruction by Google Classroom on 1st-Order Ordinally Deferential Equation at Faculty of Education, National University of Laos - ANOUVONG, Phetsavanh; BOUALONG, Leethor; PONGNATHY, Phonenaly; KEOPHATSADA , Mayouly; KEOVIENGKHON, Sonenasin (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This research aimed to 1) study on efficiency of Web-based instruction by Google Classroom on 1st-Order Ordinally Deferential Equation and 2) study on effectiveness index of Web-based instruction by Google Classroom on 1st-Order Ordinally Deferential Equation. The purpose in this research were 29 students in education program majoring in Mathematics, National University of Lao. The Experiment was used to terminize qualitative. The instruments use in this study were Web-based instruction by Google Classroom on 1st-Order Ordinally Deferential Equation totally 6 topics, and the quality evaluation questionnaire of Web-based instruction by Google Classroom on 1st-Order Ordinally Deferential Equation. Statistic for data analysis was totally, average, standard division and percent. The result of this research found that: The efficiency of Web-based instruction by Google Classroom on 1st-Order Ordinally Deferential Equation is 81.55/82.14. The effectiveness index of Web-based instruction by Google Classroom on 1st-Order Ordinally Deferential Equation is 0.76.